Dark Sweet Cherry phenolics as Dietary Chemopreventive/therapeutic Compounds for Aggressive Breast Cancer Cell Growth with No Toxicity to Normal Breast Cells (FS13-03-19). (13th June 2019) - Layosa, Marjorie Anne; Lage, Nara; Talcott, Susanne; Talcott, Stephen; Pedrosa, Maria; Chew, Boon; Noratto, Giuliana
Abstract: Objectives: Dark sweet cherries (DSC) ( Prunus avium ) contain phenolic compounds with chemopreventive and chemotherapeutic potential. This study aimed to evaluate the effect of DSC extracts in inhibiting the most aggressive breast cancer subtypes without toxicity to normal cells. Methods: DSC phenolic extracts (WE) or its fractions enriched in phenolic acids (F1), anthocyanins (F2), flavonols (F3) or procyanidins (F4) were assessed for their antiproliferative activity against the most aggressive breast cancer BT-474, MDA-MB-453, and MDA-MB-231 cell lines, and MCF-10A noncancer breast epithelial cells using the resazurin assay. Cell levels of oxidative stress were assessed with fluorescein derivative H2 DFFDA. Expression of genes linked to cell growth, apoptosis, and metastasis was assessed. Results: DSC phenolics in whole extract (WE) and fractions enriched in phenolic acids (F1), flavonols (F3) and procyanidins (F4) inhibited MDA-MB-453 with higher potency (lower IC50 values) compared to the other cell lines tested ( P  < 0.05) followed by MDA-MB-231 ∼ BT-474, without toxicity to MCF-10A cells. F3 inhibited BT-474 and MCF-10A cells with similar potency ( P  > 0.05). F2 inhibited all assessed breast cancer cell lines with similar potencies without toxicity to MCF-10A cells. Mechanisms for WE, F2 and F4 inhibitory activity on MDA-MB-453 cells were mediated by reduction of ROS (down to 28%, 56%, and 58% of control, respectively); which mediate proliferation and other events required for tumor progression. This was accompanied by downregulation of Akt/mTOR, p38, and survivin mRNA, suggesting antiproliferative and apoptotic mechanisms. An enhanced chemopreventive/chemotherapeutic potential of DSC anthocyanins is suggested because mRNA levels of invasive/metastatic biomarkers Sp1, Sp4, and VCAM-1 were downregulated only by F2. Conclusions: These results demonstrate the chemopreventive/chemotherapeutic potential of DSC phenolics and fractions enriched in anthocyanins and procyanidins as natural compounds to target cell pathways linked to proliferation, apoptosis and invasion in breast cancer. The underlying molecular mechanisms are currently under investigation. Funding Sources: This work was supported by the Northwest Cherry Growers.